The Role of lactic acid and probiotic bacteria in nutrition of honeybee colonies - Mo$1 (Bmen Zahir Mohammed Tawfik,s; Yasser Yehia Mohamed Ibrahim (2022)
(3gPg GdOQGSI JTjQ Edi JCKjQ CQHYI JQcjRGJ eNJdaI ef MeV GddGcJjc (B0.002(3, (B0.004(3, (B0.006(3, (B0.008(3% Ydi eYOd HbGA HcJjQjG (BLactobacillus acidophilus (3h (BBacillus subtilis (3ai GdeMdhd GdScQi hJCKjQ GdNdjW ef GdHcJQjG ceMaR ddfeh aj JZPjI fMd GdYSd(B. (3hjecf GdGSJfJGL ef gPg GdOQGSI Cf NdjW MeV GddGcJjc eY (BL.acidophilus (3h (BB. subtilis (3jecf GSJNOGeg ceMaR ddfeh aj JZPjI GdfMd eeG jDOj Edi GfNaGV GdQbe GdgjOQhLjfj deYOI TZGdGJ fMd GdYSd hHGdJGdj JKHjW feh GdejcQhHGJ GdeSHHI ddCeQGVs
Thesis (M.Sc.)-Cairo University-Faculty of Agriculture,2022.
Bibliography: p. 69-77.
Keywords: Beneficial insects; probiotic